A review on traditional uses, phytochemistry, and pharmacology of the genus Rourea - Che Puteh Osman, Zuriati Zahari, Mohd Ilham Adenan, Rozaini Mohd Zohdi (Journal of Applied Pharmaceutical Science, 2019)
Rourea is a genus of climbing shrubs and small trees and widely distributed in the Amazon, Pacific region, Africa, and Asia. It has about 65 species and 129 varieties. They are widely used in ethnomedicine for various health complaints such as rheumatism, diabetes, tumor, asthma, and diarrhea. This paper summarizes 38 compounds from Rourea sp. from different classes of compounds such as flavonoids, triterpenes, phenolic compounds, lipids, phytosteroids, and coumarin. Several bioactivities such as hypoglycemia, antinociceptive, antibacterial, antioxidant, antiplasmodial, and larvicidal activities are also discussed.
Keywords: Rourea, Connoraceae,flavonoids,Rourea minor, Rourea induta,ethnomedicine.